The relationship between education and self-reported mental and physical health - Amira Kurspahić-Mujčić; Amra Mujčić (Medicinski glasnik, 2018)
Aim: To investigate the relationship between educational level and self-reported physical and mental health in the population of Sarajevo Canton. Methods: This cross-sectional study was carried out in family medicine outpatient departments of the Primary Health Care Centre of Sarajevo Canton, Bosnia and Herzegovina. The study included 300 respondents who were divided into lower-and higher-education groups (?12 years and >12 years of education, respectively). The SF-36 questionnaire for self-assessment of mental and physical health and a questionnaire for the evaluation of socio-demographic characteristics were used. Results: The mean values for the mental component summary (MCS) were significantly lower in the lower education (56.86±23.02) than in the higher education group (65.08±20.91) (p=0.001). The mean values for the physical component summary (PCS) were significantly lower in the lower education (61.77 ±21.60) than in the higher education group (74.26 ±17.89) (p=0.000). On average, females had significantly lower scores than males on both the PCS (p=0.00) and the MCS (p=0.00). There was significant relationship of low education with self-reported poor mental (B=6.547, SE=2.481; p=0.009) and physical health (B=10.870, SE=2.248; p=0.024). Increased age was associated with poorer PCS and better MCS. Conclusion: Educational level is a strong determinant of perceived health. The importance of education should be emphasized to children as vitally important for their future health.
Keywords: age; schools; female; male; quality of life